HUBUNGAN KELENGKAPAN RESUME MEDIS DENGAN KETEPATAN KODE DIAGNOSIS FRACTURE DAN INJURY DI RSUD KOTA TANGERANG - Rahayu, Ade Rizqa; Temesvari, Nauri Anggita (Smart Education, 2024)
Abstract: Fracture cases in 2020 in Indonesia, which is the largest country in Southeast Asia, occurred at 1.3 million each year with a prevalence of 5.5% of the population of around 238 million. In the coding of fracture cases, inaccuracies were still found, the cause of these inaccuracies occurred because they did not add a 5-character code. So the aim of this research is to determine the relationship between the completeness of a medical resume and the accuracy of fracture and injury diagnosis codes at Tangerang City Regional Hospital. This type of research is quantitative using a cross sectional design. The sampling technique in this study used a saturated sampling technique, where the entire population in this study was sampled. The sample in this study was 68 medical resumes of fracture and injury patients. Data analysis was carried out using univariate analysis and bivariate analysis with the Chi-Square analysis test (X2). The results showed that there were 29 (42.6%) incomplete medical resumes and 39 (57.4%) complete resumes. Meanwhile, the accuracy of incorrect fracture and injury diagnosis codes was 53 (77.9%) and the accuracy of correct fracture and injury diagnosis codes was 15 (22.1%). The p-value = 0.000 (0.000 < 0.05) so there is a relationship between the completeness of the medical resume and the accuracy of the fracture and injury diagnosis code at the Tangerang City Regional Hospital. Keywords: Medical Resume, Accuracy Of Diagnosis Codes, Fractures And Injuries Abstrak: Kasus fracture tahun 2020 di Indonesia yang merupakan negara terbesar di Asia Tenggara kejadiannya sebesar 1,3 juta setiap tahunnya dengan prevalensi sebesar 5,5% dari jumlah penduduk yang berkisar 238 juta. Pada pengodean kasus fracture masih ditemukan ketidaktepatan, penyebab ketidaktepatan tersebut terjadi karena tidak menambahkan kode karakter-5. Sehingga tujuan penelitian ini adalah untuk mengetahui hubungan kelengkapan resume medis dengan ketepatan kode diagnosis fracture dan injury di RSUD Kota Tangerang. Jenis penelitian ini adalah kuantitatif dengan menggunakan desain cross sectional. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik sampling jenuh, dimana semua populasi dalam penelitian ini dijadikan sampel, sampel dalam penelitian ini sebanyak 68 resume medis pasien fracture dan injury. Analisis data dilakukan dengan analisis univariat dan analisis bivariat dengan uji analisis Chi-Square (X2). Hasil penelitian menunjukkan bahwa resume medis yang tidak lengkap sebanyak 29 (42.6%) dan resume yang lengkap sebanyak 39 (57.4%). Sedangkan ketepatan kode diagnosis fracture dan injury yang tidak tepat sebanyak 53 (77.9%) dan ketepatan kode diagnosis fracture dan injury yang tepat sebanyak 15 (22.1%). Nilai p-value = 0,000 (0,000 < 0,05) sehingga ada hubungan kelengkapan resume medis dengan ketepatan kode diagnosis fracture dan injury di RSUD Kota Tangerang. Kata kunci: Resume Medis, Ketepatan Kode Diagnosis, Fracture Dan Injury